The role of vitamin D for human health: the challenge of the right study designs and interpretation - Brenner, Hermann (Nutrients, 2023)
Numerous observational and intervention studies have suggested adverse health effects of poor vitamin D status and health benefits of vitamin D intake [...]
Veröffentlicht: 27. Juni 2023
Gesehen am 18.08.2023